A Connecticut Yankee in King Arthur's Court, Part 5. - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Connecticut Yankee in King Arthur's Court, Part 5." by Mark Twain is a historical novel published in 1889. When a Connecticut engineer named Hank Morgan suffers a head injury, he awakens in King Arthur's medieval England. Using his modern knowledge to pose as a powerful magician, he rivals Merlin and becomes the king's advisor. Hank attempts to modernize the past and implement democratic reforms, but faces opposition from the feudal system and the Church. This satirical work critiques chivalric romance while celebrating democratic values. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Connecticut_Yankee_in_King_Arthur%27s_Court
Release date is 2004-07-06
Produced by David Widger
Keywords: Fantasy fiction; Satire; Knights and knighthood -- Fiction; Arthurian romances -- Adaptations; Time travel -- Fiction; Americans -- Great Britain -- Fiction; Kings and rulers -- Fiction; Britons -- Fiction